Comparison Between Laser Lithotripsy and in Situ Eswl for Management of Lower Ureteral Calculus (Bangladesh Journal of Urology, 2020)
Objective: To compare the effectiveness of the in situ ESWL and LASER lithotripsy in the treatment of lower-ureteral calculus.Method: The study was conducted from November 2013 to October 2014 in the departments of urology, BSMMU and Dhaka Medical College Hospital. Forty four patients were selected using purposive sampling method. From selected patients 22 patients grouped as ESWL group and 22 patients grouped as LASER group. For ESWL group, patient is in supine position, stone was visualized with fluoroscopy and coupling was done. Level of shockwave energy was progressively stepped up (2000 to 2500 shocks at a frequency of 80 shocks per minute) till satisfactory stone fragmentation within patient’s comfort. On the other hand cystoscopy followed by ureteroscopy with the help of guide wire was done and stone fragmentation was achieved by LASER lithotripsy for LASER group. The follow up was done after 1 week, 1month and after 3 months. Data of the variables of interest were collected using a structured data collection format.Results: Immediate stone clearance was much higher in LASER group (90.91%) than that of ESWL group (63.63%). After one month and three months LASER group showed 95.45% stone clearance and ESWL group showed 86.36% and 90.90% stone clearance respectively. Some immediate complications found in this study were considerably higher in ESWL group than those of LASER group. Haematuria in ESWL group was 31.81% and 9.09% in LASER group. Fever was observed in 40.90% cases in ESWL group compared to 13.63% cases in LASER group. Ureteral injury was observed in 4.54% cases in LASER group compared to none in ESWL group. The complication rate was lower in LASER group (31.82%) than that in ESWL group (45.45%) but the difference was not statistically significant (P >0.05). The entire outcomes suggest that LASER lithotripsy is a better treatment option than in situ ESWL for the management of lower ureteral calculus on the basis of much higher immediate stone clearance and insignificant post operative complications.Conclusion: For treatment of lower ureteral calculus Ureteroscopic LASER lithotripsy provided significantly higher immediate stone free rate compared with in situ extra corporeal shock wave lithotripsy.Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.31-35